(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
Muscarinic acetylcholine receptors (mAChRs) (nomenclature as agreed by the NC-IUPHAR Subcommittee on Muscarinic Acetylcholine Receptors [58]) are activated by the endogenous agonist acetylcholine [63, 162] [154]. All five (M1-M5) mAChRs are ubiquitously expressed in the human body and are therefore attractive targets for many disorders. Functionally, M1, M3, and M5 mAChRs preferentially couple to Gq/11 proteins, whilst M2 and M4 mAChRs predominantly couple to Gi/o proteins. Both agonists and antagonists of mAChRs are clinically approved drugs, including pilocarpine for the treatment of elevated intra-ocular pressure and glaucoma, and atropine for the treatment of bradycardia and poisoning by muscarinic agents such as organophosphates. Of note, it has been observed that mAChRs dimerise reversibly [140] and that dimerisation/oligomerisation can be affected by ligands [193, 206].